Economic Development and the Regulation of Morally Contentious Activities - Elías, Julio J.; Lacetera, Nicola; Macis, Mario; Salardi, Paola (American Economic Review, 2017)
The regulation of many activities depends on whether societies consider them morally controversial or “repugnant.” Not only have regulation and related ethical concerns changed over time, but there is also heterogeneity across countries at a given time. We provide evidence of this heterogeneity for three morally contentious activities, abortion, prostitution, and gestational surrogacy, and explore the relationship between a country's economic conditions and how these activities are regulated. We propose a conceptual framework to identify mechanisms that can explain our findings (including the role of non-economic factors), and indicate directions for future research.